Kepemimpinan Kepala Desa dalam Meningkatkan Kinerja pada Kantor Desa Sukamaju Kecamatan Sunggal Kabupaten Deli Serdang - Louisa Novrianta Ginting; Abdul Kadir; Nina Angelia (Universitas Medan Area, 2023)
The village head acts as a leader and must have an attitude of initiative, provide solutions that can improve performance, provide direction and input that can support in carrying out the activities or tasks given. As for the problem formulation, what is the leadership role of the Village Head in Improving Performance at the Sukamaju Village Office, Sunggal Subdistrict, Deli Serdang Regency and what factors are hindering the performance of the Village Head in the Sukamaju Village Office, Sunggal District, Deli Serdang Regency. The research method used was a qualitative approach and data collection techniques used were library observation, interviews and documentation. Based on the results of the research, the leadership role of the Village Head in Improving Performance at the Sukamaju Village Office, Sunggal Subdistrict, Deli Serdang Regency by providing guidance, supervision, exemplary and motivation has generally been running quite well, but improvements must continue. The factors hindering the performance of the Village Head at the Sukamaju Village Office, Sunggal Subdistrict, Deli Serdang Regency are still lacking in leadership such as lack of objective in providing assessments of the work and assignment given, Lack of leadership skills or spirit and lack of leadership knowledge.